Study of serum albumin as surrogate marker of immune suppression in patients living with HIV and AIDS - Sharma, Shiv Shankar; Jamra, Yogendra; Hawaldar, Sanjay; Meshram, Ankit (International Journal of Advances in Medicine, 2017)
Background: HIV/AIDS being a life long illness requires regular monitoring. CD4+cell counts and HIV RNA levels have been widely accepted as the most reliable indicators of HIV disease progression but these tests are not readily available and costly too. This study examines that whether Serum albumin levels can be used as a surrogate marker for HIV disease monitoring as an alternate to CD4 cell count and HIV viral load measurements in low resource set-up. Methods: This prospective observational study was conducted at a tertiary care hospital in Central India. We studied a total of 100 PLHIV (patients living with HIV and AIDS). Correlation of CD4 count was done with serum albumin levels at baseline and at follow-up visits. Results: Several studies have suggested that albumin could serve as a useful marker of HIV disease progression in resource-limited settings. In the present study, the baseline and follow up values of albumin and CD4 counts were obtained. It was found to have a strong positive correlation amongst them with low CD4 cell counts being associated with lower serum albumin concentrations. Conclusions: The results of this study suggest that serum albumin levels have potential to be used as a surrogate low-cost prognostic marker for HIV disease monitoring in resource-limited settings where frequent estimation of CD4 cell count and HIV viral load is not possible.